2016
DOI: 10.1007/s13311-016-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Environmental Enrichment as Enablers of Task-Specific Neuroplasticity and Stroke Recovery

Abstract: Improved stroke care has resulted in greater survival, but >50 % of patients have chronic disabilities and 33 % are institutionalized. While stroke rehabilitation is helpful, recovery is limited and the most significant gains occur in the first 2-3 months. Stroke triggers an early wave of gene and protein changes, many of which are potentially beneficial for recovery. It is likely that these molecular changes are what subserve spontaneous recovery. Two interventions, aerobic exercise and environmental enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 84 publications
2
69
0
1
Order By: Relevance
“…Significant between-group differences were observed for the amount of intact tissue remaining in the cortex (F [3,26] =60.461; P<0.001), striatum (F [3,26] =209.552; P<0.001), and corpus callosum (F [3,26] =10.252; P<0.001) using 1-way ANOVA. Post hoc tests indicated that in the cortex, striatum, and corpus callosum, the sham group had significantly more intact tissue than any of the other groups (Figure 3A and 3B; P<0.05).…”
Section: Histologymentioning
confidence: 98%
See 2 more Smart Citations
“…Significant between-group differences were observed for the amount of intact tissue remaining in the cortex (F [3,26] =60.461; P<0.001), striatum (F [3,26] =209.552; P<0.001), and corpus callosum (F [3,26] =10.252; P<0.001) using 1-way ANOVA. Post hoc tests indicated that in the cortex, striatum, and corpus callosum, the sham group had significantly more intact tissue than any of the other groups (Figure 3A and 3B; P<0.05).…”
Section: Histologymentioning
confidence: 98%
“…One-way ANOVA indicated that there were significant differences in change in performance between groups (F [3,26] =3.306; P=0.036). Ryan-EinotGabriel-Welsch F post hoc analysis clearly demonstrated that the enrichment+reaching group had recovered significantly more than all other groups, even 1 month after the treatment paradigm had been terminated (P<0.05).…”
Section: Synergy Of Environmental Enrichment and Reach Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, epidemiological studies show that those living in a lower socioeconomic environments are more likely to be impacted by harmful alcohol consumption and/or obesity (Batty, Lewars, Emslie, Benzeval, & Hunt, 2008;McCartney et al, 2016;Ferraro, Schafer, & Wilkinson, 2016;Non et al, 2016). While the mechanisms underlying the detrimental neural effects of ethanol and sucrose remain unclear, the provision of environmental enrichment has been shown to be neuroprotective in rodents (Anastasía, Torre, de Erausquin, & Mascó, 2009;Barone, Novelli, Piano, Gargini, & Strettoi, 2012;Griñan-Ferré et al, 2016;Kiss et al, 2013;Livingston-Thomas et al, 2016).…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 99%
“…In the first paper in this section, Dr. Seth Hays [11] discusses combining vagus nerve stimulation, which alters cortical plasticity, with task-specific rehabilitation of motor skill for recovery of movement or auditory experience to treat tinnitus. Finally, this issue ends with a discussion by Dr. Dale Corbett and colleagues [12] on how environmental enrichment and exercise enhance many of the changes associated with spontaneous recovery. These articles detail how these interventions change the efficacy of activity-dependent plasticity within the trained circuits.…”
mentioning
confidence: 98%